A dose–response estimate for acute alcohol use and risk of suicide attempt. (10th August 2016) - Borges, Guilherme; Cherpitel, Cheryl J.; Orozco, Ricardo; Ye, Yu; Monteiro, Maristela; Hao, Wei; Benegal, Vikram
Abstract: This study reports dose–response estimates for the relative risk and population attributable risk (PAR) between acute alcohol use and serious suicide attempt. Data were analyzed on 272 suicide attempters arriving at 38 emergency departments within 6 hours of the event in 17 countries. Case‐crossover analysis, pair‐matching the number of standard drinks consumed within the 6 hours prior to the suicide attempt with that consumed during the same 6‐hour period of the previous week, was performed using fractional polynomial analysis for dose–response. Every drink increased the risk of a suicide attempt by 30 percent; even one–two drinks was associated with a sizable increase in the risk of a serious suicide attempt, and a dose–response was found for the relationship between drinking 6 hours prior and the risk of a suicide attempt up to 20 drinks. Acute use of alcohol was responsible for 35 percent PAR of all suicide attempts. While very high levels of drinking were associated with larger relative risk s of suicide attempt, the control and reduction of smaller quantities of acute alcohol use also had an impact on population levels of suicide attempt, as showed here for the first time with our PAR estimates. Interventions to stop drinking or at least decrease levels of consumption could reduce the risk of suicide attempt. Screening people more at risk to suffer these acute effects of ethanol and offering interventions that work to these high‐risk groups are a matter of urgent new research in the area. Abstract : Using data from a large and representative sample of patients from several countries and regions of the world, we found that every drink increased the risk of a suicide attempt by 30 percent, and 35 percent of all attempts were attributable to acute alcohol; even one to two drinks were associated with a sizable increase in the risk, and a dose–response was found for the relation between acute drinking and the risk of a suicide attempt up to 20 drinks.